PERKAWINAN BEDA AGAMA PERSPEKTIF NAHDLATUL ULAMA DAN MUHAMMADIYAH - Zahro, Fatimatuz (Al-Maslahah : Jurnal Ilmu Syariah, 2024)
Interfaith marriage is one of the topics in the realm of family law that is often discussed from time to time. This topic is important to discuss because it still often occurs in a plural society with various dynamics. Many scholars are of the opinion that interfaith marriage is haram or prohibited. This paper focuses on the study of interfaith marriage from the perspectives of Nahdlatul Ulama and Muhammadiyah. Nahdlatul Ulama and Muhammadiyah are the two most dominant religious organisations in Indonesia. NU is known for its tolerance towards traditions in Indonesia and Muhammadiyah is known for its purification of Islam in the world of education. This research is a library research whose primary data source is the book Bahtsul Masail and Tarjih Muhammadiyah, while secondary sources include books, journals, articles relevant to the topic discussed. The results of this study show that NU and Muhammadiyah forbid interfaith marriage because it will cause harm. NU and Muhammadiyah have different legal foundations. NU based its legal determination on the Qur'an, hadith, and ijma' of scholars, as well as classical books. In addition, the legal istinbath method used by NU is the qauli, ilhaqi, manhaji method. Meanwhile, Muhammadiyah is based on the Qur'an and hadith. The methods used by Muhammadiyah are ijma', qiyas, maslahah mursalah.